Characteristics and treatment outcomes of malnutrition among infants aged less than 6 months in North-East Nigeria (2019-2022) - Nieves Amat Camacho; Faisal Husain; Dang Bahya‐Batinda; Eithandee Aung; Abdullahi Chara; Musa Tanko; Oluwakemi F. Ogundipe; Mario Barbagallo; Kyi Htet Aung; Johan von Schreeb; Francesco Della Corte; Ourania Kolokotroni; et al. (Wiley, 2024)
Abstract Recommendations for the management of malnutrition among infants aged less than 6 months (<6 m) are based on limited evidence. This study aimed to describe the characteristics, treatment outcomes and outcome‐associated factors among malnourished infants <6 m admitted at Médecins Sans Frontières (MSF) inpatient and ambulatory therapeutic feeding centres (ITFC and ATFC) in North-East Nigeria, 2019-2022. We conducted a descriptive analysis of the cohorts and logistic regression to measure the association between two selected outcomes-inpatient mortality and defaulting from the ambulatory programme-and possible factors associated. In total, 940 infants <6 m were admitted at ITFC. Most of them presented severe acute malnutrition and comorbidities, with diarrhoea being the most frequent. On discharge, 13.3% (n = 125) of infants were cured, 72.9% (n = 684) stabilized (referred to ATFC), 6.5% (n = 61) left against medical advice and 4.2% (n = 39) died. The median length of hospital stay was 10 days [IQR 7-14]. A hospital stay shorter than 10 days was significantly associated with inpatient mortality (aOR = 12.51, 95% confidence interval [CI] = 3.72-42.11, p ≤ 0.01). Among 561 infants followed up at the ATFC, only 2.8% reported comorbidities. On discharge, 80.9% (n = 429) were cured, 16.2% (n = 86) defaulted and 1.1% (n = 6) died. Male sex (aOR = 1.94, 95% CI = 1.15-3.27, p = 0.01), internally displaced status (aOR = 1.70, 95% CI = 1.05-2.79, p = 0.03) and <−3 WLZ (aOR = 1.95, 95% CI = 1.05-3.63, p = 0.03) were significantly associated with programme defaulting. Stabilization and recovery rates among malnourished infants <6 m in the studied project align with acceptable standards in this humanitarian setting. Notable defaulting rates from outpatient care should be further explored.